2021
DOI: 10.1111/myc.13287
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal susceptibility patterns of Trichophytonbenhamiae complex isolates from diverse origin

Abstract: Background: Species from the Trichophyton benhamiae complex are mostly zoophilic dermatophytes which cause inflammatory dermatophytosis in animals and humans worldwide.Objectives: This study was purposed to (a) to identify 169 reference and clinical dermatophyte strains from the T benhamiae complex species by molecular method and adhering to the newest taxonomy in the complex (b) to evaluate the in vitro antifungal susceptibility profile of these strains against eight common and new antifungal agents that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…The rise of antifungal resistance in some dermatophytes, especially terbinafine resistance in members of the T. mentagrophytes and Trichophyton rubrum complexes, is a significant clinical problem nowadays, since it can lead to treatment failure ( 34 36 ). No antifungal resistance has been reported in members of the T. benhamiae complex ( 37 ). Several T. persicum strains have been tested in previous studies under the name T. benhamiae ( 38 , 39 ) and reidentified in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rise of antifungal resistance in some dermatophytes, especially terbinafine resistance in members of the T. mentagrophytes and Trichophyton rubrum complexes, is a significant clinical problem nowadays, since it can lead to treatment failure ( 34 36 ). No antifungal resistance has been reported in members of the T. benhamiae complex ( 37 ). Several T. persicum strains have been tested in previous studies under the name T. benhamiae ( 38 , 39 ) and reidentified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the antifungal susceptibility pattern of T. persicum does not differ from those of other species of the T. benhamiae clade. Luliconazole, efinaconazole, and terbinafine were the most potent antifungals against species from the T. benhamiae complex ( 37 ). Successful treatment of tinea corporis due to T. spiraliforme by terbinafine in this study also indicates susceptibility to this commonly used antifungal agent.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC values reported for TVB ranged from ≤0.5-4 µg/ml for N. gypsea, Microsporum species and E. floccosum, 1-16 µg/ml for T. mentagrophytes, T. interdigitale, T. tonsurans and T. rubrum (the main agents of onychomycosis), 38 8->16 for Fusarium species 39 and 1-16 µg/ml for the emerging Trichophyton species in the T. benhamiae clade. 13 In our evaluation the MIC values ranged from 1-8 µg/ml for N. gypsea and N. fulva, and 2-4 µg/ml for other species which is not a significant difference. Natural resistance to TVB rarely occurs in dermatophytes and moreover, given…”
Section: Ta B L E 1 Information Of the Geophilic Dermatophyte Species...mentioning
confidence: 52%
“…Nevertheless, in agreement with the results of recent investigations that found the in vitro activities of LUL, TER and EFN superior to other medications against Trichophyton species, the present study supports and extends such finding to geophilic species from the genera Nannizzia and Arthroderma. 9,11,13,14 Of the topical antifungal agents CPO, LUL, EFN and TVB tested in the present survey, the best results were observed with LUL, which had the lowest geometric mean MIC for all tested isolates. Luliconazole (LUL) is an imidazole antifungal drug that in 2013 was approved by FDA as a 1% topical cream for treatment of skin infections by dermatophytes.…”
Section: Discussionmentioning
confidence: 66%
“…Recently, terbinafine-resistant strains of T. mentagrophytes have been isolated, showing that antifungal resistance is an emerging threat among dermatophytes [20]. This underlines the importance of correct taxonomic identification, even though at present no difference in antifungal susceptibility has been observed among species from the T. benhamiae complex [21].…”
Section: Introductionmentioning
confidence: 99%